2021
DOI: 10.1111/jnc.15496
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous, transient adenosine release is not enhanced in the CA1 region of hippocampus during severe ischemia models

Abstract: Adenosine is an endogenous neuromodulator and its concentration increases in the extracellular space after ischemia, causing neuroprotective effects (Melani et al., 2012). Administration of exogenous adenosine showed protection against CA1 hippocampal cell death and supported functional recovery following cerebral ischemic injury (Seydyousefi et al., 2019). While basal adenosine levels in the brain are in the nanomolar range (Melani et al., 2012), during ischemia, extracellular adenosine levels increased sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…The recovery ability of VD rats is mainly associated to the operation method and the postoperative rest time. 4VO is a modeling method that has a greater effect on rat trauma and death, and the recovery difficulty of this method should be greater than that of 2VO, EO, and MCAO (Ganesana and Venton, 2021 ). Tuo et al ( 2021 ) found that 8-week to 3-month resting after modeling, cerebral blood flow in rats could restore to normal.…”
Section: Discussionmentioning
confidence: 99%
“…The recovery ability of VD rats is mainly associated to the operation method and the postoperative rest time. 4VO is a modeling method that has a greater effect on rat trauma and death, and the recovery difficulty of this method should be greater than that of 2VO, EO, and MCAO (Ganesana and Venton, 2021 ). Tuo et al ( 2021 ) found that 8-week to 3-month resting after modeling, cerebral blood flow in rats could restore to normal.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Journal of Neurochemistry, Ganesana and Venton (2021) report on spontaneous adenosine release as a potential mechanism of brain tissue defense in ischemic conditions. Adenosine, an endogenous neuromodulator and a homeostatic modulator controlling many brain functions, exerts its effects through its multiple receptors.…”
Section: Adenos Ine Rele a S E A S A P Otentially Neuroprotec Tive Me...mentioning
confidence: 99%
“…In their study, Ganesana and Venton (2021) selected the CA1 area of the hippocampus, an area most susceptible to ischemia, to explore rapid changes in spontaneous, transient adenosine. To associate changes in adenosine release with ischemia severity, they performed a comparative study of transient adenosine event frequency and adenosine concentration in three stroke models with different ischemia intensity.…”
Section: B R Ain Ischemia Fail S To Induce Adenos Ine Rele a S E In H...mentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid adenosine acts as a neuromodulator, signaling through receptors to modulate blood flow, the sleep–awake cycle, pain, and memory. Adenosine receptors are located both presynaptically and postsynaptically and adenosine often has an overall inhibitory effect, acting at A 1 receptors to dampen dopamine, glutamate, and GABA neurotransmission. The hippocampus CA1 region is an important region for adenosine neuromodulation, as adenosine inhibits excitatory synaptic transmission during ischemia. There is a high frequency and concentration of adenosine transient events in the hippocampus CA1 region, and the CA1 may be susceptible to ischemic damage because adenosine transient events do not increase during ischemia . Exogenous adenosine protects hippocampal neurons from death during cerebral ischemic injury, but the endogenous pool of adenosine is depletable in the CA1 …”
Section: Introductionmentioning
confidence: 99%